Can’t we negotiate the importance of electron correlation? HF vs RIMP2 in ab initio quantum mechanical charge field molecular dynamics simulations of Cu+ in pure liquid ammonia - Saputri, Wahyu Dita; Pranowo, Harno Dwi; Hofer, Thomas S. (elsevier, 2022)
The impact of electron correlation in quantum mechanical charge field molecular dynamics (QMCF MD) simulations of Cu+ in pure liquid ammonia has been investigated by comparing the results obtained at the Hartree–Fock (HF) level and via resolution-of-identity second order Møller–Plesset perturbation theory (RIMP2). To achieve a manageable computational demand, a rigid-body solvent model was employed to describe the NH3 molecules. The solvation structures observed in both cases have similar characteristics in which tetrahedral [Cu(NH3)4]+ dominates with average CuAN distances of 2.24 (HF) and 2.12 (RIMP2) Å, respectively. The ligand dynamics in the first solvation shell of the RIMP2 simulation are notably higher than in the HF case and resulted in the formation of an intermediate [Cu(NH3)3]+ complex along the sampling period. Electron correlation effects were found to mainly impact the solvent–solvent hydrogen bonding interaction, thereby providing a more accurate description of the structural properties in terms of the average CuAN distances along with greatly enhanced ligand exchange dynamics occurring between the first and second solvation shell.